Impact of Financial Risk on Profitability: Evidence from Nigerian Deposit Money Banks - Bello, Musa Muhammad; Isah, Nasiru; Salihi, Awaisu Adamu (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2024)
The paper assesses the influence of financial risk on profitability of listed Nigerian Deposit money banks (DMBs). Profitability was proxied with return on assets (ROA), whereas financial risk as a predictor is measured with Liquidity Risk (LQR), Interest Rate Risk (IRR) and Operational Risk (OPR). The population of the study is all fourteen (14) Nigerian DMBs as at 31St December 2022 out of which twelve (12) DMBs were used for the analysis. Correlational research design was used, and data were generated from secondary sources, basically from the annual reports and accounts of twelve listed deposit money banks from 2013 to 2022. Descriptive statistics, correlation analysis as well as panel corrected standard error regression were utilized as tools of analysis for the study. The findings reveal that Liquidity risk and Operational risk has a positive and significant relationship with profitability measured by ROA of listed deposit money banks in Nigeria, while interest rate risk has a positive and insignificant relationship with profitability of listed deposit money banks in Nigeria. The positive and significant effect of liquidity risk on profitability means that listed DMBs are able to meet their obligations as at when due. Also, the result of operational risk on profitability indicates that increase in operational risk decreases profitability of listed DMBs. The positive effect of interest risk on profitability means that increase in interest rate increase profitability.